Exploring electronic cigarette portrayals: a content and thematic analysis of African online news coverage - Chimwemwe Ngoma; Yusuff Adebayo Adebisi (Substance Abuse Treatment, Prevention, and Policy, 2023)
Abstract Background Electronic cigarette use has surged internationally in recent years, with numerous countries noting an uptick in users. Despite this, the portrayal of e-cigarette usage in African news remains unclear. Methods This research investigates the subject, employing a mixed-methodology approach. The study units were news articles on electronic cigarette use retrieved from AllAfrica, an online African news archive. A total of 38 online news and opinion articles published between June 2017 and June 2022 qualified the exclusion and inclusion criteria. A content analysis revealed prevalent codes and themes, while a thematic analysis explored the association between news sources and framing. Results The results indicate that articles and arguments presenting e-cigarettes positively outnumber those with a negative slant. The health impacts of electronic cigarettes emerged as the most discussed topic, with health authorities frequently cited as news sources. However, these health authorities often lacked a unified stance on e-cigarette safety. Conclusion The lack of consensus among health officials could have public health consequences, possibly resulting in the formulation of uninformed policies.